Desmopressin testing in children with von Willebrand syndrome in haemostaseologic centers of Saxonia, Saxonia-Anhalt and Thuringia - Huhn, B.; Hofmann, A.; Hofmann, K.; Sirb, H.; Aumann, V.; Kentouche, K.; Sauerbrey, A.; Franke, D.; Kuhlisch, E.; Knöfler, R. (Hämostaseologie, 2009)
The influence of desmopressin on hemostasis is mediated by the release of von Willebrand factor and of coagulation factor VIII from vascular endothelium. The necessity of testing desmopressin effectiveness on hemostasis is a matter of controversy and the performance of the test is not yet standardized. For this reason the desmopressin tests in 114 children with von Willebrand syndrome (type 1, n=98; type 2A, n=12; type 2M, n=2; type 2N, n=2) carried out in 7 paediatric haemostaseologic centers were retrospectively analyzed. The effectiveness of desmopressin was assessed using defined response criteria. As expected, the test performance showed a wide variation among the centers. In 99 children desmopressin was given intravenously as a short infusion at a dosage ranging from 0.25 to 0.41 μg/kg and in 15 intranasally at an absolute dose of 40 to 300 μg. The points of time for blood taking after desmopressin application ranged from 0.5 to 12 h. The absent desmopressin response in 7 patients (6%) and the partial response in 15 indicate the necessity of testing desmopressin effectiveness before the first therapeutic use. The application of desmopressin was well tolerated by the patients.
Keywords: Desmopressin testing; von Willebrand syndrome; children